Pengaruh Hedonic Shopping Motivation, Flash Sale, Dan Viral Marketing Terhadap Impulse Buying Pada Konsumen E- Commerce Shopee - Dita, Oktaviani Marsha; Handrijaningsih, Lies; Putri Ekanova, Angga; Anisah, Anisah; Mariani, Septi (Universitas Gunadarma, 2025)
Technological developments have had a significant impact on buying and selling transactions through marketplace platforms such as e-commerce Shopee. Shopee offers various interesting and popular products in Indonesia. This research aims to analyze the influence of hedonic shopping motivation, flash sales, and viral marketing on impulse buying among Shopee consumers, both simultaneously and partially. The research results show that hedonic shopping motivation, flash sales, and viral marketing have a simultaneous or partial effect on impulse buying. And the Flash sale variable is the most dominant variable in impulse buying among Shopee consumers